Toughening of interface networks through the introduction of weak links. (15th August 2021) - Chiu, Edwin; Demkowicz, Michael J.; Srivastava, Ankit
Abstract: The resistance of polycrystalline materials to intergranular fracture depends on the toughness of the interfaces between neighboring grains. Using finite element simulations on model, two-dimensional microstructures, we demonstrate that the steady-state crack growth resistance of a polycrystal that contains exclusively high toughness interfaces is suboptimal: its crack growth resistance may be increased by introducing a minority fraction of weak interfaces at random locations within the interface network. Furthermore, the weaker are these interfaces, the greater is their toughening effect. These weak interfaces toughen the material through crack deflection and branching, nucleation of secondary cracks, and inelastic dissipation within intact interfaces. Our findings suggest that fracture resistance-oriented material development should not aim to eliminate all weak interfaces, but rather judiciously incorporate a low fraction of them. Graphical Abstract: Image, graphical abstract